Если враг не сдается: [роман] / М. П. Нестеров - Нестеров Михаил Петрович (Спецназ ГРУ, 2003)
Экземпляры: АБ (20190109) / Инвентарный номер: 40689 / Цена: 53.30 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Н 56 / ББК: 84(2Рос=Рус)6